KOMPOSITUM DALAM FILM GAME OF THRONES SEASON 8 KARYA DAVID BENIOFF DAN D. B. WEISS - Tambajong, Kevin Christofel; Lotulung, Donald R.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research entitled â€œKompositum dalam film Game of Thrones Season 8â€, and is written to fulfill the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities, Sam Ratulangi University. The aims of this study is focused on the process in forming of compound words used in film Game of Thrones Season 8. In analyzing the compound word process, the writer uses Oâ€™Gradyâ€™s (1997:143) theory of compound words. Compounding is a process of combining some lexical categories (nouns, adjectives, verbs or prepositions) (Oâ€™Grady 1996: 26). The result from each compound words in this reseach are vary. In compound nouns there are five forms: Noun+Nounâ†’Noun, Verb+Verbâ†’Noun, Adjective+Nounâ†’Noun, Adjective+Verbâ†’Noun, Adjective+Noun â†’Noun. In compound verbs there are two forms: Noun+Nounâ†’Verb, Verb+Nounâ†’Verb. In compound Adjective there are four forms: Noun+Adjectiveâ†’Adjective, Verb+Nounâ†’Adjective, Adjective+Adjectiveâ†’Adjective, Adjective+Nounâ†’Adjective. In compound adverb there are six forms: Noun+Advebâ†’Adverb, Verb+Adverbâ†’Adverb, Adjective+Adjectiveâ†’Adverb, Adverb+Nounâ†’Adverb, Preposition+Nounâ†’Adverb, Preposition+Verbâ†’Adverb. The writer took forty-nine compound words used in film Game of Thrones Season 8 for six episodes. A morphological analysis used by the writer to analyze the compound words, classify the types and the meaning of compound words. The writer found four kinds of compound words in the films with different kind of form in each compound words. For compound noun there are five forms, two forms of compound verb, four forms of compound adjective and six forms on compound adverb. From forty-nine compound words found in the films, there are thirty compound nouns, two compound verbs, nine compound adjectives, and eight compound adverbs. Also there are two form of endocentric and three form of exocentric found in this research. It is indicated that there are a lot of compound words that can be found in the films.Keywords: Morphology, Compound Words, Compounding, Type of compound, Game of Thrones Season 8.